A noção de excessus em Tomás de Aquino (STh. q. 84, a. 7 ad 3) sobre a crítica de Cornelio Fabro a Karl Rahner - Sousa, Luis Carlos Silva de (2011)
The aim of the thesis is to examine the notion of excessus in the Suma de Teologia (Ia, q. 84, a. 7 ad 3) by Thomas Aquinas, through Cornelius Fabro s critique of Karl Rahner. With the analysis of the notion of excessus we tackle the problem concerning the possibility knowing of God. The hypothesis we raised initially with Cornelio Fabro is that Rahner's interpretation of notion of excessus as anticipation (Vorgriff) does not preserve the transcendence of God. Karl Rahner's commitment to the anthropocentric change would distort the original meaning of excessus as an overtaking or transcendence, which comes from Dionysus, in the line of the "negative theology": the mediation of the transcendental subjectivity that would eventually immanentalize the esse of God in thought. It is not our intention to analyze, however, if Fabro s "principle of immanence" applies or not to Rahner, but only to certify that Rahner reinterprets Sto. Thomas. In fact, Fabro and Rahner part from different perspectives when they approach the text of Thomas Aquinas, the real "touchstone" of our investigation.We do not intend to examine whether Karl Rahner, in his own way (that is, with features including those that were not extracted from Thomas Aquinas text), in fact preserves the divine transcendence. From the historical point of view (which is ours), Fabro is right to stress that the notion of excessus in Thomas Aquinas comes from Dionysus, but it is wrong not to recognize the legitimate role that the negative judgement exerts on the nonquiddidative knowledge of God. We conclude with a critique of the critique of Fabro, because, in criticizing what he understands by pseudo-Thomism in Rahner, he eventually affects Thomas Aquinas himself